Puritanism Values Of The New England Society Reflected In Nathaniel Hawthorne's The Scarlet Letter 1850): A Sociological Approach - IZZATUL CH, NAILA (2012)
The objective of this research is to analyze the structural element of the novel and describes the Puritanism values of the New England society which is reflected Hawthorne's The Scarlet Letter based on the sociological approach. The object of this research is The Scarlet Letter novel that is created by Nathaniel Hawthorne in 1850. This research paper is qualitative research by descriptive analysis. The datum of this research is divided into two parts. They are the primary data and secondary data. The primary data are taken from the book of this novel, The Scarlet Letter. The researcher uses the novel that was published by Oxford University Press in 2007. The secondary data is taken from some source such as the literary books, articles from internet, and else. The research comes to the following conclusions. Firstly, based on the structural analysis, it is apparent that in this novel Nathaniel Hawthorne delivers a moral message that each society holds its custom, and each custom has its own values. Secondly, based on the sociological analysis, it is evident that the production of The Scarlet Letter was closely related to the social background of the New England community at that time.